Transportation and Differentiation on Rhythmicity of Road Traffic Activities Between Urban and Rural Areas - Nguyen, Ngoc Thi (Indonesian Journal of Geography, 2024)
Transport and rhythm in transport activities are considered as a mirror reflecting socio-economic activities. In addition to studying secondary sources, the article mainly uses field methods and counts the number of vehicles circulating on 12 main urban routes and 12 inter-district routes along with the interviews of random 200 workers in the transport sector, traders, and sales staff in Thanh Hoa province. The data sources are synthesized, processed and compared to see the differentiation in the number of means of transport in urban areas, revealing it is 2.0 times higher than that in rural areas. The rhythm in transport activities in urban areas is also often more concentrated than in rural areas. In addition, during production and business seasons such as tourist season, agricultural harvest season, and holidays, the volume of transport, turnover and transport revenue is always 3 - 5 times higher than normal. The results of the study contribute to orienting transport operation plans to avoid the consequences of traffic congestion during peak times of the year.